Effect of fiber-matrix interaction and embedment length on the pullout behavior of rice straw fibers embedded in clay matrix - Oswaldo Hurtado-Figueroa; Humberto Varum; María Isabel Prieto; Romel J Gallardo Amaya; Alfonso Cobo Escamilla (Results in Engineering, 2025)
Earth as a building material is considered an environmentally friendly alternative for implementation in modern construction. The improvement of mixtures with clay matrix presents advances in their mechanical resistance by adding vegetable fibers as reinforcement. Some research concludes its results based on destructive testing without a thorough analysis of fiber-matrix interaction. In the present study, fiber-matrix interaction phenomena were analyzed using the single-fiber pullout test. The test was performed on rice straw fibers mercerized in 1 %, 2 %, and 3 % NaOH solutions embedded 5 mm, 10 mm, and 15 mm in a clay matrix stabilized with Carboxymethylcellulose and Cassava starch. The importance of NaOH treatment improving the surface roughness of the fibers was demonstrated. The surface modification favored the adhesion of the matrix to the fiber causing opposition to detachment. The geometrical irregularities of some fibers caused friction phenomena that required higher forces than those exerted in the initial detachment. The fibers treated in 1 % NaOH solution with an exposure time of 1 hour and embedded for 10 mm showed higher initial detachment force and opposition to displacement due to friction phenomena. The rigidity of the straw treated with 2 % NaOH solution for 2 h prevented its confinement by shrinkage due to drying of the matrix, a phenomenon that facilitated its extraction due to minimal opposition to friction. The low bonding stress of the plant fibers with the clay matrix favors the semi-ductile behavior of the green composite The single-fiber pullout test on vegetable fibers embedded in clay matrixes allows for identifying the fiber-matrix interaction and the optimal working length.